The Paradoxical Foundation of Strategic Management - Rasche, Andreas (Contributions to Management Science, 2008)
This book offers a systematic critique of the scientific discourse of strategic management. It uncovers scholars' unquestioned assumptions and shows that by upholding these assumptions reseachers obscure the paradoxical nature of strategic reasoning. To uncover the paradoxes of strategic management the author refers to the philosophy of Jacques Derrida. He exposes the paradoxes that inevitably occur when theorizing about corporate strategy along the dimensions strategy context, process, and content and shows how these paradoxes can enrich future thinking about strategic problems. The analysis is completed by a discussion of theoretical and practical implications which highlight the need to research strategy not as something an organization has, but as something an organization does. Such a 'practice perspective' gives reference to the paradoxical ground that strategic management rests on and enriches scholars' ability to reflect on practitioners' tasks while 'doing' strategy in organizations.